2011
DOI: 10.3126/ajms.v2i1.4290
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Anti-Retroviral Therapy among People Living with HIV and AIDS in Far West, Nepal

Abstract: Objective: Adherence to Anti-Retroviral Therapy is a principal predictor for the success of Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) treatment. It remains as a challenge to AIDS treatment and care with the wide spread of the associated risks. The study aims to assess adherence level and factors associated with adherence to Anti-Retroviral Therapy (ART) among people living with HIV and AIDS in Far West, Nepal. Material & Methods:A cross sectional study was carried out in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 13 publications
5
17
1
Order By: Relevance
“…ART adherence in this study is consistent with previous, similar studies in Nepal, and is comparable to self-reported ART adherence in several other low- and middle-income countries 3,17,19,20. The slightly higher ART adherence in this study might be due the assessment of 7-day adherence.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…ART adherence in this study is consistent with previous, similar studies in Nepal, and is comparable to self-reported ART adherence in several other low- and middle-income countries 3,17,19,20. The slightly higher ART adherence in this study might be due the assessment of 7-day adherence.…”
Section: Discussionsupporting
confidence: 91%
“…However, the 13% non-adherence observed in the present study constitutes a serious problem in a resource-limited country like Nepal, as the development of treatment resistance will lead to increased hospitalization rates, increased health care costs, reduced productivity, disruption of families and communities, and increased morbidity and mortality. The main reasons participants gave for non-adherence were simply forgetting to take ART and having a busy schedule, which is in accordance with previous findings 12,19,23,24…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…7 Similar to other studies sex, educational status, occupation were not affecting adherence to ART. 5,7 Age and ethnicity are significantly associated with drug adherence. Family history of HIV and Family History of ART are not associated to drug adherence as contrast to study conducted by Saha.…”
mentioning
confidence: 99%